Analysis of Spatial Characteristic of Maritime Weather in Java Sea - Rachmad Andri Atmoko; Aulia Siti Aisjah; Gunawan Nugroho (IPTEK Journal of Proceedings Series, 2015)
Sea transportation continuity is mainly affected by the sea weather. The sea voyage may be disturbed by the unpredictable weather pattern. The rate of shipping accident that is caused by the bad weather shows a high percentage. Accordingly, the study of java sea wave characteristic is required. The java sea waters especially in the north side of Java Island, between Surabaya, Semarang Banjarmasin and Makassar is one of the most dense shipping lanes in Indonesia. Several big harbors such as tanjung perak of Surabaya and tanjung emas of Semarang serve high frequency of stevedoring and passenger loading/unloading. In previous researches, the sea weather predictor of java sea waters is still temporal. In this research, numerical modeling of SWAN is used to models the sea wave propagation direction and significant height of the wave in java sea waters. This model uses the concept of spectral energy balance to describe physical interaction that happened in the sea. Two scenarios are applicated in this simulation. in the first scenario, the input of wind speeds are given from 4 direction (west, north, east and south), while in the second scenario, the wind speeds are given according to the character of seasonal winds of the research object area.